2022
DOI: 10.1038/s41598-022-23598-8
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer analysis of the role of hexokinase II (HK2) in human tumors

Abstract: More and more evidence show that HK2 is closely related to tumors. But no pan-cancer analysis is available. This paper aimed to explore the potential roles of HK2 across thirty-three tumors based on the datasets of the cancer genome Atlas (TCGA) and gene expression omnibus. HK2 is highly expressed in most tumors and related to the progression of some tumors. HK2 expression was associated with the infiltration of T follicular helper cells for the TCGA tumors of uveal melanoma, breast invasive carcinoma (BRCA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…This in-silico approach should explain, at least in part, the in-vitro assays, which were based on the quantification of cell viability. For this reason, some of the molecular targets highly expressed in a variety of cancer cells and related to this process are those belonging to the Bcl-2 family (Mcl-1 and Bcl-xL) [ 46 ], anti-apoptotic proteins, and hexokinase 2 (HK2), which plays a central role in the cellular uptake and utilization of glucose [ 47 ]. The anti-apoptotic Bcl-2 proteins protect against cell death by apoptosis and also allow senescent cells to survive [ 48 ], and it has been suggested that they might appear in the early phase of carcinogenesis in the stomach [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This in-silico approach should explain, at least in part, the in-vitro assays, which were based on the quantification of cell viability. For this reason, some of the molecular targets highly expressed in a variety of cancer cells and related to this process are those belonging to the Bcl-2 family (Mcl-1 and Bcl-xL) [ 46 ], anti-apoptotic proteins, and hexokinase 2 (HK2), which plays a central role in the cellular uptake and utilization of glucose [ 47 ]. The anti-apoptotic Bcl-2 proteins protect against cell death by apoptosis and also allow senescent cells to survive [ 48 ], and it has been suggested that they might appear in the early phase of carcinogenesis in the stomach [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of Kaplan–Meier plots derived from data on 1925 lung cancer patients clearly confirmed the strong oncogenic role of HK2, LDHA, PHGDH, PSAT1, SHMT2, MTHFD2, c-Myc, and ATF4 (CREB-2) in lung cancer. The high expression of genes coding for all of these enzymes and their transcriptional regulators is strongly associated with a shortened patient survival in different types of malignancies [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high expression of HK2 has been observed in the majority of tumors, and this increase in HK2 levels has been correlated with the progression of tumors. Additionally, HK2 expression has been related to immune cell infiltration, such as T follicular helper cells (Tfh) [10].…”
Section: Metabolic Changes Of Cancer Cellsmentioning
confidence: 99%